Visual arts teacher education observatory: a study of the materiality of the working conditions of art teachers in Brazil (Palíndromo, 2022)
This study aims to systematize the bases for analysis of the 803 questionnaires that were answered by Basic Education teachers who work teaching art in school. The team network project Observatory of Teacher Education in the field of Arts Education: Comparative Studies Brazil and Argentina, from two working groups, organized the process of data analysis. The bibliographic study was used as a research procedure, as well as the analysis of the methodological process of data collection and pre-organization, as a phase prior to the analysis. The bibliographical study intended to reflect on the materiality of the working conditions of the art teacher. As a result of this phase, it was possible to perceive the need for data formatting to use the NVIVO software, as well as identifying that the precariousness of work and lack of public policies are fundamental elements for the analysis process, because it directly invol[1]ves the pedagogical work. It is true that the appreciation of the teacher and of art and the investment in pedagogical work are constituted both by legal aspects and by the praxis that develops within the scope of the characteristics of teaching. However, investment in professional qualification, in access to art and culture, as well as in working conditions, are determining factors for professionals in the field of arts at school to fulfill their social role. Therefore, educational praxis cannot be dissociated from the conditions that the state performs in fulfilling its obligations related to the quality of Public Education.
Keywords: Pedagogical work; Visual arts; Teacher education